Development and Characterization of Transgenic Sugarcane with Insect Resistance and Herbicide Tolerance - Wang, Wen Zhi; Yang, Ben Peng; Feng, Xiao Yan; Cao, Zheng Ying; Feng, Cui Lian; Wang, Jun Gang; Xiong, Guo Ru; Shen, Lin Bo; Zeng, Jun; Zhao, Ting Ting; Zhang, Shu Zhen (Frontiers in Plant Science, 2017)
Genetically modified crops which had been commercial applied extensively majorly are the insect resistance and herbicide tolerance events. In this study, the Bt insecticidal gene Cry1Ab, the glyphosate-tolerant gene EPSPS, and the selection marker gene PMI were combined into a single transferred DNA fragment and introduced into sugarcane by Agrobacterium-mediated transformation. Thirty-three resistant plantlets were obtained after selection using a PMI/mannose selection system. Thirty of these resistant plantlets were PCR positive for the three target genes. Southern blot assay revealed that the copy number of the integrated fragment in the transformed plantlets varied from 1 to 7. ELISA analysis showed that 23 of the 33 resistant plantlets expressed Cry1Ab and EPSPS protein. Five single-copy and ELISA-positive transgenic lines were tested under laboratory and field conditions to determine their resistance to insects and herbicides, and also evaluated their agronomic characteristics and industrial traits. Bioassay under laboratory conditions showed that larvae that fed with fodder mixture containing stem tissues from all single-copy transgenic lines were weak and small; Moreover, pupation and eclosion were delayed significantly. And in the field condition none of transgenic sugarcane was destroyed by the cane borer while more than 30% of wild type sugarcane was destroyed by cane borer. For herbicide resistance, the transgenic plantlets grew healthy even when treated with up to 0.5% roundup while wild type plantlets would die off when treated with 0.1% roundup. Thus demonstrate that these transgenic lines showed strong insect resistance and glyphosate tolerance under both laboratory and field conditions. But in the field most of the transgenic plants were shorter and more slender than non-transformed control plants. So they presented poor agronomic characteristics and industrial traits than non-transformed control plants. Thus, a considerable number of embryogenic calli should be infected to obtain transgenic lines with potential for commercial use.